CORPORATE CULTURE OF A HIGHER EDUCATION INSTITUTION AS A FACTOR IN FORMING STUDENTS’ PROFESSIONAL IDENTITY - Blynova, Olena; Lappo, Violetta; Kalenchuk, Valentyna; Agarkov, Oleg; Shramko, Ihor; Lymarenko, Lidiia; Popovych, Ihor (Revista Inclusiones, 2020)
The purpose is to examine the features of the correlation between the evaluations of corporate culture by university students and their professional identity. Corporate culture of a university is considered as an integral system of standards, rules, beliefs, values and behavior patterns of its participants. Corporate culture determines the uniqueness of a university among other educational institutions. The paper establishes correlation between the students’ perceptions of the university corporate culture with organizational identity (p≤.05). The study investigates the variable “organizational identity” as an intermediary between the university corporate culture and the students’ professional identity. The research determines that the students’ evaluation of the university corporate culture affects organizational identity, and through it – professional identification of future specialists. Comparative analysis of the ideas about the real and desired images of corporate culture of a higher education institution proves that a hierarchical, bureaucratic model corresponds to organizational culture of the university; a democratic, collaborative model (р < .05) corresponds to the desired image of organizational culture. The students’ self-identification with the university community has a positive correlation with their professional identification.